THE IMPLEMENTATION OF BUSINESS ETHICS IN THE PALM OIL INDUSTRY - Felix Wisnu Isdaryadi (Modus, 2015)
Abstract Palm oil is the most produced vegetable oil in the world today-approximately 37 million metric tons, andis entirely GMO-free. Oil palm produces up to 10 times more oil per hectare than soybean, rapeseed or sunfower. Although oil palm is a more sustainable source of vegetable oil than other oil crops, there is concern that the growing demand of palm oil for food and bio fuel could lead to rapid and ill-managed expansion of palm oil production and result in serious environmental and social consequences. It is vital that the production and use of palm oil must be done in a sustainable manner based on economic, social and environmental viability. It becomes clear that these actions are benefcial on one hand, but, on the other hand, might be harmful in the long run. The palm oil industry may result in rapid economic growth. However, it could also degrade the environment, whichin turn could lead to public health problems in the longer term, decreasethe productivity and harm the economy.Keywords: palm oil industry, business ethics, environment, economy.